Identifying anaesthetic risks in pregnant surgical patients - Nelles, Janet (Operating Room Nurses Association of Canada Journal, 1989)
The expectant arrival of a newborn is often the most exciting time a family can enjoy. However, pregnancy can precipitate medical conditions neces- sitating surgery. Trauma cannot be excluded simply because pregnancy exists. Literature suggests that approximately 0.2% to 2% of North American women will undergo surgery for conditions unrelated to their pregnancy. 2:4 Women of childbearing age are increasingly remaining in the workforce and continue to work until the final stages of pregnancy. The continuing trend for women to assume employment responsibility traditionally held by men, increases the risk for trauma during pregnancy. This paper will examine special considerations for the pregnant surgical patient, focusing on aspects prior to labour and delivery. The pregnant woman presents the surgical team with special considerations not only for the well-being of maternal health but fetal health as well.